Restoring Fire-Grazer Interactions to Pursue Heterogeneity in Sandhills Prairie - Arterburn, Jack R.; Twidwell, Dirac; Wonkka, Carissa L.; Schacht, Walter H.; Wedin, David A. (Frontiers in Ecology and Evolution, 2019)
Heterogeneity has emerged as a fundamental principle for grassland management and the importance of environmental heterogeneity for biological diversity has raised questions about the appropriateness of grassland practices that seek to promote uniform grassland structure and composition. Principles of uniformity in grassland management reflect a utilitarian target of “managing for the middle” by minimizing both overgrazing and underutilization while avoiding or preventing fire and other disturbances that consume aboveground biomass. We evaluated pioneering efforts to restore fire-grazer interactions via patch burning in an effort to increase spatial heterogeneity at the patch scale in the Nebraska Sandhills, a sandy soil, mixed-grass ecoregion with a long history of “management for the middle.” The application of patch burning did not increase heterogeneity of vegetation structure or composition at the patch-level in the Nebraska Sandhills. Instead, grassland structure exhibited greater temporal variability between growing and dormant seasons and smaller scale variability within fire patches. The low stocking rate and the rapid regrowth of live herbaceous vegetation following fire likely constrained the degree of spatial heterogeneity observed in our study and highlights the challenges of balancing forage supply and demand in semi-arid grasslands.